Electrophoretic Characterization of Foot-and-Mouth Disease Virus-Specific Ribonucleic Acid - Arlinghaus, Ralph B. (1969)
Foot-and-mouth disease virus (FMDV)-specific ribonucleic acid (RNA) was analyzed by electrophoresis on 0.5% agarose gels. Four classes of RNA were resolved as a function of mobility in agarose: two classes of slowly migrating multistranded RNA, the infectious viral RNA with intermediate mobility, and a minor fast-moving class of lower-molecular-weight single-stranded RNA. The major RNA species were infectious viral RNA and the slowest migrating class of multistranded RNA. The latter RNA was polydisperse when analyzed by sucrose gradient centrifugation, it was partially ribonuclease resistant, and it was the predominant RNA species labeled during the initial period of (3)H-uridine triphosphate incorporation in the cell-free system. Heat treatment studies indicated that part of the slowest-moving RNA was degraded at 60 C and almost complete degradation was detected at 100 C. It was concluded that this RNA is the replicative intermediate in viral RNA synthesis. The second class of multistranded RNA contained both a ribonuclease-resistant RNA and a second RNA peak which was detected only after heat treatment at temperatures above 75 C. Fractions of FMDV-specific RNA isolated by sucrose gradient centrifugation were analyzed by agarose-gel electrophoresis. Infectious viral RNA was detected only in the 37S zone and was the major species of RNA in this part of the gradient. The ribonuclease-resistant RNA (the 20S zone) contained about equal amounts of multistranded RNA (both classes) and the low-molecular-weight single-stranded RNA. All sucrose gradient fractions between 20 and 40S were found to contain the replicative intermediate, although the major portion was detected in the 20 to 25S region.